1997
DOI: 10.1136/jcp.50.6.490
|View full text |Cite
|
Sign up to set email alerts
|

CD31 (JC70) expression in plasma cells: an immunohistochemical analysis of reactive and neoplastic plasma cells.

Abstract: Aims-To investigate the immunohisto-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…CD31 was also positive in staining the CD138 immunoreactive plasma cells, but CD34 and Factor VIII were negative. Positive immunohistochemical staining for CD31 has previously been reported in reactive extramedullar plasma cells [4]. This was demonstrated in the present study in the plasma cell rich granulation tissue ( fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…CD31 was also positive in staining the CD138 immunoreactive plasma cells, but CD34 and Factor VIII were negative. Positive immunohistochemical staining for CD31 has previously been reported in reactive extramedullar plasma cells [4]. This was demonstrated in the present study in the plasma cell rich granulation tissue ( fig.…”
Section: Discussionsupporting
confidence: 74%
“…Bronchoscopy and cytological examinations are often negative. Percutaneous needle biopsy may induce a diagnostic dilemma because of the difficulty to differentiate inflammatory pseudotumour from fibrohistiocytic neoplasms, nodular sclerosing Hodgkin's lymphoma, primary lung cancer and especially fibrosing mediastinitis [4]. In addition, due to the specific unilateral localisation of the lesion in the present case, fibrosing mediastinitis is less probable.…”
Section: Discussionmentioning
confidence: 69%
“…It is sensitive and much more specific than CD34. However, it has been reported to react with plasma cells, 138 macrophages, 139 and some carcinomas and mesotheliomas 140 . Fli‐1, a new marker for PNET, is also a good marker for vascular tumours with a good sensitivity 84 .…”
Section: Sarcomas For Which Ihc Is Determinant For the Diagnosismentioning
confidence: 99%
“…Previous studies have suggested that PECAM-1 may be expressed on CD19-positive B cells derived from bone marrow (17), reactive plasma cells defined by CD38…”
mentioning
confidence: 99%